In Vitro and In Vivo Assessment of Pulmonary Risk Associated with Exposure to Combustion Generated Fine Particles - Fahmy, Baher (2010)
Strong correlations exist between exposure to PM(2.5) and adverse pulmonary effects. PM(2.5) consists of fine (≤2.5 μm) and ultrafine (≤0.1 μm) particles with ultrafine particles accounting for >70% of the total particles. Environmentally persistent free radicals (EPFRs) have recently been identified in airborne PM(2.5). To determine the adverse pulmonary effects of EPFRs associated with exposure to elevated levels of PM(2.5), we engineered 2.5 μm surrogate EPFR-particle systems. We demonstrated that EPFRs generated greater oxidative stress in vitro, which was partly responsible for the enhanced cytotoxicity following exposure. In vivo studies using rats exposed to EPFRs containing particles demonstrated minimal adverse pulmonary effects. Additional studies revealed that fine particles failed to reach the alveolar region. Overall, our study implies qualitative differences between the health effects of PM size fractions.